The insecticidal toxin genes of Yersinia enterocolitica are activated by the thermolabile LTTR‐like regulator TcaR2 at low temperatures. Issue 4 (16th July 2013) - Starke, Mandy; Richter, Marleen; Fuchs, Thilo M.
Summary Temperature‐dependent activation of bacterial virulence factors at 37°C is well investigated. The molecular mechanism underlying the expression of toxicity determinants at environmental temperatures, however, has not been characterized. The insecticidal activity of Yersinia enterocolitica strain W22703 requires the toxin complex subunit A (TcaA) encoded on the pathogenicity island Tc‐PAIYe. Genes tcaA and tcaB encoding this subunit are maximally produced at low temperatures (10–20°C), but repressed at body temperature. Two further insecticidal genes, tcaC (subunit B) and tccC1 (subunit C), are silent at both temperatures. A novel LysR‐type transcriptional regulator (LTTR), TcaR2, revealed to be autoregulated and essential for tcaA and tcaB expression in W22703. Expression of tcaR2 is negatively controlled by a second LTTR‐like regulator, TcaR1. Gel mobility shift assays confirmed the interaction of TcaR2 with the tcaR2, tcaA and tcaB promoters. The activity of the tcaA promoter in heterologous hosts in the presence of TcaR2 excludes the requirement of additional, Yersinia‐specific (co)factors for toxin gene expression. Overproduced TcaR2 protein is shown to be unstable at 37°C, whereas the mRNA of tcaA and tcaR2 is equally stable at low and high temperature. Thus, TcaR2 is a key player in the induction of insecticidal genes in Y. enterocolitica at low temperatures.